The Feminization Of Local Politics: Practices, Representation, And Resistance In The Masculine Arena Of Village Government - Tasya, Amalia (Journal of Politica Governo, 2025)
This study aims to analyze the practice of political feminization in village government, focusing on the role of women in male-dominated local politics and the challenges they face in confronting patriarchal structures. Although women's participation in village governance is increasing, entrenched patriarchal structures remain limited space for women to make significant political decisions. In this context, political feminization contributes to a shift in policy priorities and a more inclusive and collaborative leadership style. However, the main challenge women face are the cultural and systemic barriers that limit their access to power. Although gender quotas and affirmative policies provide opportunities for women, their effectiveness is highly dependent on women's ability to leverage their positions in local political structures. The study concludes that to achieve deeper gender equality, structural changes in social norms are needed, as well as increased educational and economic access for women. The feminization of local politics is not only about numerical representation, but also about empowering women in the process of making policies that are more responsive to their needs.